Long-term control of vulval lichen sclerosus after treatment with a potent topical steroid cream. - Dalziel, K; Wojnarowska, F (1993)
Super potent topical steroids are an effective treatment for many patients with vulval lichen sclerosus, but concerns exist about their long-term safety. Review of 12 women up to 39 months following a course of super potent topical steroids shows that subsequent control of disease activity and symptoms is much easier than before therapy, with most patients requiring only small amounts of moderate potency topical steroid. Apart from a background erythema no long term cutaneous side effects were observed.